Menggugah Rasa Nyata pada Lingkungan Virtual: Aplikasi Material Virtual pada Museum Real-Virtual - Citadewi, Pande Kadek Ariati; Hayati, Arina; Dinapradipta, Asri (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 11 No 1 (2024): April 2024DO - 10.24843/JRS.2024.v11.i01.p09, 2024)
In this digital era, museum as an institution increasingly incorporates virtual technology into their exhibitions and architectural elements. The application of virtual materials in museums allows sensory variations that enrich visitors’ experience. A sense of realness needs to be considered in a museum environment, with virtual materials as its constituent elements that can arouse the emotional involvement of visitors. This paper investigates virtual materials’ applications and a sense of realness qualities in real-virtual museum architecture. It employs a qualitative research strategy with in-depth interviews and precedent studies used as data collection techniques and content analysis as its analyzing method. Study results show that the principle of immersion to arouse a sense of realness in a real-virtual museum environment includes sensory richness, interaction, and coherence. Integrating real-virtual elements can be carried out within architectural formal and spatial elements’ design. Integration with architectural formal elements includes using interactive surfaces and surface projections, while integration with architectural spatial elements includes the application of motion and audio sensors. These integrations can be implemented in architectural design by isolating virtual devices from outdoor distractions like light, sound, humidity, and temperature. Keywords: immersion; materiality; museum; realness; real-virtual   Abstrak Di era digital ini, museum sebagai sebuah institusi mulai menggunakan teknologi virtual pada konten pameran dan elemen arsitekturnya. Aplikasi material virtual dalam arsitektur museum memberikan kemungkinan variasi sensoris yang memperkaya pengalaman dari para pengunjung museum. Kualitas rasa nyata atau realness perlu dipertimbangkan dalam lingkungan atau ‘arsitektur’ dengan pemanfaatan material virtual sebagai elemen penyusunnya, sehingga arsitektur ini dapat menggugah keterlibatan pengunjung secara emosional. Paper ini bertujuan untuk merumuskan keterlibatan material virtual dan kualitas rasa nyata yang sebaiknya diaplikasikan pada arsitektur real-virtual museum . Tulisan ini menerapkan strategi penelitian kualitatif, dengan memilih wawancara mendalam sebagai teknik pengumpulan data, dan  konten analisis sebagai metode analisisnya. Hasil studi menunjukkan bahwa prinsip immersion untuk menggugah rasa nyata pada lingkungan museum real-virtual meliputi kekayaan sensoris, interaktif, serta koheren. Integrasi material virtual dan elemen arsitektur dapat dilakukan dalam lingkup elemen formal dan ruang. Integrasi dengan elemen ruang meliputi penggunaan permukaan interaktif dan proyeksi permukaan, sedangkan integrasi dengan ruang meliputi aplikasi sensor gerak dan audio. Integrasi ini bisa diimplementasikan dalam desain arsitektur dengan mengisolasi perangkat virtual dari distraksi outdoor termasuk visual cahaya, suara, kelembapan, dan suhu dari ruang luar. Kata kunci: immersion ; materialitas; museum; realness; real-virtual